Intensification of steam explosion and structural intricacies impacting sugar recovery. (October 2017) - Gaur, Ruchi; Semwal, Surbhi; Raj, Tirath; Yadav Lamba, Bhawna; Ramu, E.; Gupta, Ravi P.; Kumar, Ravindra; Puri, Suresh K.
Graphical abstract: Highlights: Single-stage steam explosion utilized for high sugar recovery from CS. Hot water extraction of CS prior to SE improved the glucan conversion by 38%. Incorporating DA in extraction medium further increased glucan conversion by 30%. Xylo-oligomers inhibited enzymatic hydrolysis evident by post washing experiments. SA1-RT-200 reduced the CrI, G-lignin & xylan content leading to 79.3% C6 recovery. Abstract: Dilute acid (DA) pretreatment at pilot level failed for cotton stalk (CS) due to the technical issues posed by its inherent nature. Reasonable glucan conversion has been reported via two-stage pretreatment but adds on to the process cost. Proposed herewith is a single-stage steam explosion (SE) process preceded by water extraction resulting in high sugar recovery from CS. Raising the extraction temperature to 80 °C increased the glucan conversion from 37.9 to 52.4%. Further improvement up to 68.4% was achieved when DA was incorporated during the room temperature extraction. LC-MS revealed the formation of xylo-oligomers limiting the glucan conversion in proportion to the length of xylo-oligomers. Varying extraction conditions induced structural alterations in biomass after SE evident by compositional analysis, Infrared Spectroscopy, X-Ray Diffraction and Scanning Electron Microscopy. Overall glucose recovery, i.e. 75.8–76.7% with and without DA extraction respectively was achieved.